PENGARUH PAJAK, RETRIBUSI, DBH, BELANJA MODAL, DAN PERTUMBUHAN EKONOMI TERHADAP KEMANDIRIAN DAERAH - Maya Novitasari; Lita Novitasari (Universitas PGRI Madiun, 2019)
This research is to empirically prove the influence of Local Taxes, Regional Levies, Revenue Sharing Funds, Capital Expenditures, Economic Growth on Regional Financial Independence in Regencies / Cities in East Java Province 2014-2017 period. The analytical method used in this study is a quantitative method with multiple regression tests, by conducting the Classical Assumption test first before reaching the best study model. The total population of this study is 38 districts / cities consisting of 29 districts and 9 cities in East Java Province. The sampling technique is to use a census. The results of this study are: Regional Taxes, Regional Levies, and Capital Expenditures affect the Regional Financial Independence, Revenue Sharing and Economic Growth does not affect the Regional Financial Independence. Simultaneously the Regional Tax, Regional Retribution, Revenue Sharing Funds, Capital Expenditures, and Economic Growth influence the Regional Financial IndependenceKeywords: Regional Taxes, Regional Retribution, Revenue Sharing Funds, Capital Expenditures and Economic Growth, Regional Financial Independence.